Buton, Islamization, and this Manuscript Tradition - Ali Rosdin (International Journal of Nusantara Islam, 2014)
Buton the beginning of the country is filled with myths, which serves to form a world view of cosmocentric in determining descriptions of time, space, and society. Buton as a kingdom lasted for over two centuries (1327-1541) and then continued with a sultanate era for more than four centuries (1541-1960). During the era of the kingdom, Buton was not acquainted with script and literary tradition. Apparently, tradition of writing manuscript was firstly known in the sultanate era, when the process of Islamization began by the scholars who introduced the tradition of reading and writing the Arabic script, which was later modified into a Buton script (Buri Wolio). Sultanate built on the basis of ideology of Islam and Sufism applied teachings of “martabat tujuh” on the system and structure of government. The manuscripts tradition achieved its golden peak in the reign of the 29th Sultan, La Ode Muhammad Idrus Kaimuddin (1824-1851), which was instituted in a Zawiah school. Today, there are about 340 texts in Buton manuscripts, which are mostly found in the collections of Abdul Mulku Zahari. In addition, there are still many other texts may be found on varied other private collections, which the numbers are difficult to determine because of various reasons.